Lack of nucleotide polymorphism in the Y-linked sperm flagellar dynein gene dhc-Yh3 of Drosophila melanogaster and D. simulans. - Zurovcova, M.; Eanes, W.F. (Genetics, 1999)
We studied levels of intra- and interspecific nucleotide variation associated with a Y-linked gene in five members of the Drosophila melanogaster subgroup. Using published sequence for 348 bp of the Dhc-Yh3 gene, and degenerate PCR primers designed from comparisons of the sea urchin and Chlamydomonas flagellar dynein genes, we recovered a 1738-bp region in D. melanogaster. Analyses of sequence variation in a worldwide collection of 11 lines of D. melanogaster and 10 lines of D. simulans found only a single silent polymorphism in the latter species. The synonymous site divergence per site for Dhc-Yh3 is comparable to values for X and autosomal genes. Assuming a Wright-Fisher population model, the lack of variation is statistically less than expected using appropriately reduced estimates of theta from the X and autosomes. Because the Y chromosome encodes only six known genes, genetic hitchhiking associated with background selection is unlikely to explain this low variation. Conversely, adaptive hitchhiking, as associated with sex-ratio chromosomes, or a large variance in male fertility may reduce the polymorphism on the Y chromosome. Codon bias is very low, as seen for other genes in regions of low recombination.